Aplicación de la Conciliación al delito de Violencia Psicológica contra la mujer o miembros del núcleo familiar en Ecuador. - Concha Mendoza, Alison Jamilex (2023)
As a result of an increased number of complaints reaching the Prosecutor's Office without a sentence, the following research, titled "Application of Conciliation to the crime of Psychological Violence against women or family members in Ecuador". Approximately 70% of these cases are filed because the victim fails to attend the proceedings requested. Conciliation must therefore be investigated to what extent it is necessary and in which cases it can be applied. In order to determine if the parties are capable of reaching an agreement, a multidisciplinary team consisting of clinical and educational psychologists should be in charge of determining whether or not the principle of voluntariness prevails, thus, that family ties do not disintegrate. Within the framework of the present research, it gathers several research materials such as several digital and physical bibliographies, as well as national and comparative legislation that is in force, which contributes to the discussion that has been raised. Likewise, the methods used included scientific, inductive, deductive, analytical, exegetical, comparative, and statistical methods. Finally, since the research work is of a critical-legal nature, the documentary technique was used to understand the scope of the theoretical appraisals, as well as the limitations as to which cases the application of this mechanism is viable or not, complemented by interviews with legal professionals, In these interviews, it was reinforced how important it is to study this crime and the consequences of its mishandling, in terms of the punishment given to the aggressor, the vulnerability left behind by the victim, and the disintegration of the family. This background allowed to make a critical-legal analysis of the contradictions that exist in some norms such as the Constitution, the Organic Code of the Judicial Function and the Organic Code of the Integral Penal Code, which allowed to legally support why its application would be possible.